Re-Applying the Basic Psychological Needs in Exercise Scale to Various Portuguese Exercise Groups: An Analysis of Bifactor Models and Contextual Invariance. Issue 4 (August 2021) - Rodrigues, Filipe; Cid, Luis; Teixeira, Diogo; Monteiro, Diogo
This research explored the nature of basic psychological needs in physical activity settings by applying relatively advanced methodological procedures for psychometric assessment. We first re-examined the Basic Psychological Needs in Exercise Scale (BPNES) by reviewing its applicability for physical activity domains among Portuguese respondents. We demonstrated the use of Bifactor Confirmatory Factor Analysis (CFA) and Exploratory Structural Equation Modeling (ESEM) and discussed the practical implications of these models. Next, we tested contextual measurement invariance in order to examine needs universality. Our participants were gym exercisers (n = 1935), physical education students (n = 1449), and athletes (n = 1631), all of whom completed the adapted and validated version of the scale in their respective practice physical activity domains. All models under analysis displayed acceptable to excellent fit; the bifactor ESEM model displayed the best fit. We conducted ancillary bifactor measures to assess scale dimensionality and found that the BPNES is best interpreted as a multidimensional instrument. Through testing for multigroup analysis, the bifactor ESEM did not show contextual invariance. In conclusion, the BPNES should be predominantly used as a multidimensional instrument when assessing basic needs in separate physical activity domains. Basic psychological needs are perceived differently between seemingly similar physical activity contexts. Researchers should measure basic needs as a global factor and use context validated sub-scales.